Modelling numerical simulation of DP590 steel undergoing finite strain deformation of uniaxial tensile test - Kamarulzaman, M. F.; Zin, N. M.; Mohd Nor, M. K.; Samad, M. S. A. (2022)
Metal sheets made of Advanced High Strength Steel (AHSS) of Dual Phase (DP) steels are commonly utilised in the automobile industry to form numerous complex forms and sizes of components specifically related to crash energy management. In this paper, the deformation behaviour of DP 590 at various strain rates (0.0001, 0.001, 0.01 and 0.1 s−1) along two principal directions; 0° and 90° are simulated. The tensile behaviour of DP590 was captured in terms of stress-strain curves using the simplified Johnson-Cook (JC) of LS Dyna Finite Element code. The engineering data was first characterised to output the material parameters of JC model which were used further to predict the strain rate dependency of DP590 at various strain rates along the principal directions. A good agreement was obtained in each test.